2020
DOI: 10.31557/apjcp.2020.21.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Studies Provide Insight into Possible Target and Mechanisms of Action of Nobiletin against Cancer Stem Cells

Abstract: Recent studies have shown that the ability of tumors to develop and propagate depends on a small population of cells called cancer stem cells (CSCs) (Pan et al., 2018; Zhu and Fan, 2018). CSCs are responsible for resistance to chemotherapy and radiotherapy (Toledo-Guzman et al., 2018). Conventional chemotherapy has proved to be able to reduce tumor size; however most of the tumor relapsed because the population of CSCs that were able to survive and grow into tumor bulk (Zhu and Fan, 2018). The CSC-targeted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Our GCP model consists of 9 prognostic genes which could be regarded as promising therapeutic targets for precision treatment in GC. There are plenty of experimental evidences have suggested that some of these 9 genes including DDX24 [ 39 , 40 ], TTF2 [ 14 , 15 ], SSX4 [16] , ACLY [41] , [42] , [43] , [44] , VPS35 [45] , [46] , [47] , [48] , DCTN2 [49] , [50] , [51] , [52] and MRPL4 [ 53 , 54 ] played important roles in development and progression in many tumor types. However, there was few report about ARGLU1 functions in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our GCP model consists of 9 prognostic genes which could be regarded as promising therapeutic targets for precision treatment in GC. There are plenty of experimental evidences have suggested that some of these 9 genes including DDX24 [ 39 , 40 ], TTF2 [ 14 , 15 ], SSX4 [16] , ACLY [41] , [42] , [43] , [44] , VPS35 [45] , [46] , [47] , [48] , DCTN2 [49] , [50] , [51] , [52] and MRPL4 [ 53 , 54 ] played important roles in development and progression in many tumor types. However, there was few report about ARGLU1 functions in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular localization analysis was performed with Wolfpsort subcellular localization predication software 36 . GO, KEGG pathway and domain enrichment analyses were carried out by DAVID tool with corrected p-value below 0.05 37 . The two-tailed Fisher’s exact test was applied to check the Khib proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The two-tailed Fisher’s exact test was applied to check the Khib proteins. Multiple testing correction was performed using the Benjamini–Hochberg false discovery rate (FDR) control method 37 . The images of the significantly pathways were obtained from KEGG.…”
Section: Methodsmentioning
confidence: 99%
“…These studies highlight the potential of NOB in disease treatment and its protective effects. The newly published articles have shed some light on the capability of NOB in cancer therapy [80,81]. In the present review, we attempt to mechanistically examine the efficiency of NOB in cancer therapy by focusing on molecular pathways and mechanisms.…”
Section: Therapeutic and Biological Activities Of Nobmentioning
confidence: 99%